Educational technology: Guidance on self-care for elderly patients discharged from the medical clinic to their homes (Research, Society and Development, 2022)
Objective: To develop an educational booklet for self-care guidance to elderly patients at discharge from the medical clinic to their homes. Method: This is an action research with a quanti-qualitative approach developed at the FSCMP in the medical clinic sector.  The study population was 84 elderly patients with self-care deficit, in the process of discharge to their homes.  For data collection, a semi-structured instrument was applied, including sociodemographic, economic and clinical data, hospitalization, self-care ability, perceptions about hospital discharge and difficulties in self-care. The interviews were processed according to Bardin's content analysis method. Quantitative variables were distributed in absolute and relative frequencies. Results: The sample predominated elderly male (66.67%), age range of 65 to 69 years (42.85%), family income of up to 01 minimum wage (53.57%), stable union (33.33%), education degree of elementary school (61.91%), brown (78.54%) and retired (41.67%). Most of them have a prolonged hospitalization time, 33.34% of them for more than 30 days, 77.38% are polypharmacists, and 46.43% have a significant dependence. The most evident diagnosis was digestive system disease (42.85%). As for the understanding of hospitalization and hospital discharge, the meanings that the subjects attributed were classified into three thematic categories: A-The importance of family/caregivers support; B-Family financial maintenance; C-General self-care referred. Conclusion: There is a need for further studies and construction of more types of products with educational technologies that seek to cover the largest possible amount of self-care guidance to post-hospital discharge elderly patients.